Serotonin modulation in the male Aedes aegypti ear influences hearing - Xu, Yifeng Y. J.; Loh, YuMin M.; Lee, Tai-Ting; Ohashi, Takuro S.; Su, Matthew P.; Kamikouchi, Azusa (Frontiers in Physiology, 2022)
Male Aedes aegypti (Ae. aegypti) mosquitoes rely on hearing to identify conspecific females for mating, with the male attraction to the sound of flying females (‘phonotaxis’) an important behavior in the initial courtship stage. Hearing thus represents a promising target for novel methods of mosquito control, and hearing behaviors (such as male phonotaxis) can be targeted via the use of sound traps. These traps unfortunately have proven to be relatively ineffective during field deployment. Shifting the target from hearing behavior to hearing function could therefore offer a novel method of interfering with Ae. aegypti mating. Numerous neurotransmitters, including serotonin (5-hydroxytryptamine, or 5-HT) and octopamine, are expressed in the male ear, with modulation of the latter proven to influence the mechanical responses of the ear to sound. The effect of serotonin modulation however remains underexplored despite its significant role in determining many key behaviors and biological processes of animals. Here we investigated the influence of serotonin on the Ae. aegypti hearing function and behaviors. Using immunohistochemistry, we found significant expression of serotonin in the male and female Ae. aegypti ears. In the male ear, presynaptic sites identified via antibody labelling showed only partial overlap with serotonin. Next, we used RT-qPCR to identify and quantify the expression levels of three different serotonin receptor families (5-HT1, 5-HT2 and 5-HT7) in the mosquito heads and ears. Although all receptors were identified in the ears of both sexes, those from the 5-HT7 family were significantly more expressed in the ears relative to the heads. We then thoracically injected serotonin-related compounds into the mosquitoes and found a significant, reversible effect of serotonin exposure on the male ear mechanical tuning frequency. Finally, oral administration of a serotonin-synthesis inhibitor altered male phonotaxis. The mosquito serotonergic system and its receptors thus represent interesting targets for novel methods of mosquito, and thus disease, control.